2015
DOI: 10.7189/jogh.06.010401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mHealth interventions for maternal, newborn and child health in low– and middle–income countries: Systematic review and meta–analysis

Abstract: ObjectiveTo assess the effectiveness of mHealth interventions for maternal, newborn and child health (MNCH) in low– and middle–income countries (LMIC).Methods16 online international databases were searched to identify studies evaluating the impact of mHealth interventions on MNCH outcomes in LMIC, between January 1990 and May 2014. Comparable studies were included in a random–effects meta–analysis.FindingsOf 8593 unique references screened after de–duplication, 15 research articles and two conference abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
324
2
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(355 citation statements)
references
References 39 publications
17
324
2
12
Order By: Relevance
“…11,12 However, most of the studies in this area are of poor methodologic quality, and few have evaluated the effects on client health outcomes. 12,13 This cluster-randomized clinical trial sought to determine the effect of an mHealth training tool for birth attendants in lowincome countries, the safe delivery app (SDA), on the knowledge and skills of health care workers in neonatal resuscitation and perinatal mortality.…”
mentioning
confidence: 99%
“…11,12 However, most of the studies in this area are of poor methodologic quality, and few have evaluated the effects on client health outcomes. 12,13 This cluster-randomized clinical trial sought to determine the effect of an mHealth training tool for birth attendants in lowincome countries, the safe delivery app (SDA), on the knowledge and skills of health care workers in neonatal resuscitation and perinatal mortality.…”
mentioning
confidence: 99%
“…These authors concluded that the emerging focus on strong experimental research designs, combined with government involvement and integration of mHealth interventions into the healthcare system, was a positive development, and augured well for the field, a marked departure from the conclusion of Lee et al [21]. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the establishment of the Millennium Development Goals (MDG) in 2,000 and the Sustainability Development Goals (SDG) in more recent times the healthcare sector in developing countries has witnessed the introduction of various mHealth technologies [8,9]. Numerous mHealth technologies were introduced (cf.…”
Section: Mobile Health (Mhealth) In Developing Countriesmentioning
confidence: 99%